Adapting to the motion of multiple independent targets using multileaf collimator tracking for locally advanced prostate cancer: Proof of principle simulation study. Issue 1 (23rd November 2020) - Hewson, Emily A.; Ge, Yuanyuan; O'Brien, Ricky; Roderick, Stephanie; Bell, Linda; Poulsen, Per R.; Eade, Thomas; Booth, Jeremy T.; Keall, Paul J.; Nguyen, Doan T.
Abstract : Purpose: For patients with locally advanced cancer, multiple targets are treated simultaneously with radiotherapy. Differential motion between targets can compromise the treatment accuracy, yet there are currently no methods able to adapt to independent target motion. This study developed a multileaf collimator (MLC) tracking algorithm for differential motion adaptation and evaluated it in simulated treatments of locally advanced prostate cancer. Methods: A multi‐target MLC tracking algorithm was developed that consisted of three steps: (a) dividing the MLC aperture into two possibly overlapping sections assigned to the prostate and lymph nodes, (b) calculating the ideally shaped MLC aperture as a union of the individually translated sections, and (c) fitting the MLC positions to the ideal aperture shape within the physical constraints of the MLC leaves. The multi‐target tracking method was evaluated and compared with two existing motion management methods: single‐target tracking and no tracking. Treatment simulations of six locally advanced prostate cancer patients with three prostate motion traces were performed for all three motion adaptation methods. The geometric error for each motion adaptation method was calculated using the area of overexposure and underexposure of each field. The dosimetric error was estimated by calculating the dose delivered to the prostate, lymph nodes, bladder, rectum, and small bowel using a motion‐encoded dose reconstruction method. Results: Multi‐target MLC tracking showed an average improvement in geometric error of 84% compared to single‐target tracking, and 83% compared to no tracking. Multi‐target tracking maintained dose coverage to the prostate clinical target volume (CTV) D98% and planning target volume (PTV) D95% to within 4.8% and 3.9% of the planned values, compared to 1.4% and 0.7% with single‐target tracking, and 20.4% and 31.8% with no tracking. With multi‐target tracking, the node CTV D95%, PTV D90%, and gross tumor volume (GTV) D95% were within 0.3%, 0.6%, and 0.3% of the planned values, compared to 9.1%, 11.2%, and 21.1% for single‐target tracking, and 0.8%, 2.0%, and 3.2% with no tracking. The small bowel V57% was maintained within 0.2% to the plan using multi‐target tracking, compared to 8% and 3.5% for single‐target tracking and no tracking, respectively. Meanwhile, the bladder and rectum V50% increased by up to 13.6% and 5.2%, respectively, using multi‐target tracking, compared to 2.7% and 1.9% for single‐target tracking, and 11.2% and 11.5% for no tracking. Conclusions: A multi‐target tracking algorithm was developed and tracked the prostate and lymph nodes independently during simulated treatments. As the algorithm optimizes for target coverage, tracking both targets simultaneously may increase the dose delivered to the organs at risk. Abstract :